Perceived climate change impacts and adaptation responses in ten African mountain regions - Cuni-Sanchez, Aida; Aneseyee, Abreham B.; Baderha, Ghislain K. R.; Batumike, Rodrigue; Bitariho, Robert; Imani, Gerard; Jha, Nisha; Kaganzi, Kaiza R. (Nature Climate Change, 2025)
Mountain regions are particularly vulnerable to climate change impacts. Yet, little is known about local adaptation responses in African mountain regions, especially if these are incremental or transformational. First, using household questionnaires, we interviewed 1,500 farmers across ten African mountain regions to investigate perceived climate change impacts and adaptation responses. Second, through a reflective process involving all co-authors, we identified: (1) main constraints and opportunities for adaptation, and (2) if adaptation was incremental or transformational. Questionnaire data show that farmers in all sites perceive multiple impacts, and that they mostly respond by intensifying farming practices and using off-farm labour. We established that, while several constraints were shared across sites, others were context specific; and that adaptation was mostly incremental, but that certain attributes (for example, social capital) made three sites in East Africa slightly more transformational.
Keywords: Mountain regions; Climate change; Impacts; Adaptation responses